0.15(40)+0.05c=0.25(40+c)

Simple and best practice solution for 0.15(40)+0.05c=0.25(40+c) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.15(40)+0.05c=0.25(40+c) equation:


Simplifying
0.15(40) + 0.05c = 0.25(40 + c)

Multiply 0.15 * 40
6 + 0.05c = 0.25(40 + c)
6 + 0.05c = (40 * 0.25 + c * 0.25)
6 + 0.05c = (10 + 0.25c)

Solving
6 + 0.05c = 10 + 0.25c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-0.25c' to each side of the equation.
6 + 0.05c + -0.25c = 10 + 0.25c + -0.25c

Combine like terms: 0.05c + -0.25c = -0.2c
6 + -0.2c = 10 + 0.25c + -0.25c

Combine like terms: 0.25c + -0.25c = 0.00
6 + -0.2c = 10 + 0.00
6 + -0.2c = 10

Add '-6' to each side of the equation.
6 + -6 + -0.2c = 10 + -6

Combine like terms: 6 + -6 = 0
0 + -0.2c = 10 + -6
-0.2c = 10 + -6

Combine like terms: 10 + -6 = 4
-0.2c = 4

Divide each side by '-0.2'.
c = -20

Simplifying
c = -20

See similar equations:

| 5k+21=6 | | .4998x^4-.5x^2+.4998=0 | | 10x+1=-8x+5 | | 6f+2f-5+3= | | x-0.1=-0.375 | | 16x+20x=180 | | 1x-5=2x-12 | | x/21=14 | | -2(-5)=x | | -4x-6=-5x+11 | | 3(2y+1)=5(y-2)+16 | | -2(-5)=1 | | -2=x/-5 | | 6f+2f-3+8= | | X+20=5x-20 | | 10x-8=10x+6 | | 33=K+41 | | 8k-8+3k-14= | | 3.5=x-4.6 | | 4x-12=6x+42 | | 4x-3=3x-9 | | 5x^2+3=18 | | 3c-5=2c+15 | | cosx=-4 | | 3=2c+15 | | 6v-8=5v-18 | | 5x^2+10=4x^2+15 | | 12y-(12+6y)=3(y+5) | | -2x+5=8x-10 | | 9t=6(5/2-t) | | (1/64)=2^y | | 40=-2t^2+2t+40 |

Equations solver categories